2014
DOI: 10.4172/hccr.1000114
|View full text |Cite
|
Sign up to set email alerts
|

Health Services Researcher Pathway For Registered Nurses: An Integrative Literature Review

Abstract: Background: Research competencies across nurses' career stages have not been adequately explored. Yet, research skills to appraise, synthesize, and implement research findings are required for evidence-based practice.Purpose: To explore the literature on registered nurse research competencies; to identify core competencies (i.e., knowledge, skills, and attitudes), research capacity-building activities, strategies and recommendations to strengthen nurses' research capacity; and to propose a conceptual developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Regarding knowledge, the emphasis seems to be on knowledge of KT science, followed by knowledge of different sources of evidence. This finding is consistent with previous studies that found overlap between KT competencies and research competencies, 56,74,75 suggesting that KT competencies encompass more than research competencies for understanding the local context where the KT processes take place. However, a major gap was found in ETOs on providing knowledge about the different KBs-related roles (the five main brokering roles).…”
Section: Kbs Competenciessupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding knowledge, the emphasis seems to be on knowledge of KT science, followed by knowledge of different sources of evidence. This finding is consistent with previous studies that found overlap between KT competencies and research competencies, 56,74,75 suggesting that KT competencies encompass more than research competencies for understanding the local context where the KT processes take place. However, a major gap was found in ETOs on providing knowledge about the different KBs-related roles (the five main brokering roles).…”
Section: Kbs Competenciessupporting
confidence: 92%
“…This highlights the overlap between research skills and KT skills. 56,74,75 However, it is important to emphasize that there is a shortage of ETOs available to equip participants with communication and mediation skills; this is problematic considering that KBs need to be skillful in negotiating complex environments when promoting evidence-based decision-making. 79 Developers of ETOs may have deliberately omitted those skills because KBs tend to naturally possess basic communications and networking skills.…”
Section: Kbs Competenciesmentioning
confidence: 99%